Late-onset tacrolimus-induced encephalopathy in lung transplant recipient: Case report - Qiaoyan Lian; Lulin Wang; Peihang Xu; Li Wei; Shouning Zhou; Xiuhua Li; Xin Xu; Jianxing He; Chunrong Ju (Heliyon)
Background: Tacrolimus is regarded as a cornerstone of immunosuppressive therapy after lung transplantation. Tacrolimus-induced neurotoxicity is common, while late-onset severe encephalopathy is rare. Case presentation: We report a case of a 61-year-old woman who presented with confusion and limb stiffness 29 months after undergoing bilateral lung transplantation for bronchiectasis. She received immunosuppressive regimen consisting of low-dose tacrolimus, sirolimus, mycophenolate mofetil, and prednisone due to renal insufficiency. Neurological examination revealed gaze deviation towards the right side in both eyes, as well as nuchal rigidity. The muscle strength of her extremities was at grade 1–2, and muscle tone was increased, with a bilateral positive Babinski sign. Blood tests revealed that tacrolimus and sirolimus levels were within the therapeutic range. Brain magnetic resonance imaging revealed that periventricular white matter lesions were slightly more extensive than those observed prior to transplantation. Lumbar puncture showed that cerebrospinal fluid pressure and composition were normal. A diagnosis of tacrolimus-induced encephalopathy was made after a thorough clinical examination. Subsequently, cyclosporine was administered instead of tacrolimus for anti-rejection therapy, and she has remained free of neurological symptoms since then. The improvement of clinical symptoms following the withdrawal of tacrolimus supports the drug-induced etiology of this neurological disorder. Conclusions: We highlight that tacrolimus-induced encephalopathy can occur in a late stage after lung transplantation and may occur with tacrolimus whole blood concentrations within the therapeutic range.